PATHOMORPHOLOGICAL CHARACTERISTICS OF THE ADRENAL GLANDS IN RESPIRATORY DISTRESS SYNDROME IN DEEPLY PRETERM NEWBORNS - Zubtiyev, Сардор (International Journal of Scientific Pediatrics, 2025)
The article focuses on the pathomorphological characteristics of the adrenal glands in deeply premature newborns suffering from respiratory distress syndrome (RDS). Purpose of the work: to analyze the pathomorphological alterations in the adrenal glands of deeply preterm newborns with RDS, highlighting their impact on disease progression. Material and methods: the study was based on adrenal gland samples obtained during autopsies of deeply preterm newborns with RDS who passed away within 0–7 and 8–28 days of life. Histological analyses were conducted using standard staining methods (hematoxylin-eosin and Sudan III), alongside morphometric evaluation. Results and discussion: significant structural changes in the adrenal glands of preterm newborns with RDS were identified: a) cortical atrophy: thinning of the fasciculata and reticular zones, indicating reduced glucocorticoid synthesis; b) cellular degeneration: increased apoptosis and necrosis in cortical cells, likely resulting from hypoxia-induced damage; c) vascular abnormalities: venous congestion, edema, and microhemorrhages in the parenchyma; d) reduced lipid content: substantial depletion of lipid vacuoles, reflecting impaired steroidogenesis.These findings indicate severe adrenal dysfunction, further exacerbating the insufficiency of adaptive mechanisms in preterm newborns with RDS. Conclusions: pathomorphological alterations in the adrenal glands of deeply preterm newborns with RDS include cortical atrophy, cellular degeneration, vascular abnormalities, and reduced lipid content. Such changes significantly weaken adrenal function, aggravating the severity of RDS. The findings provide valuable insights for developing diagnostic and therapeutic strategies aimed at enhancing adrenal function and adaptive responses in deeply preterm newborns.